Problematika Pembelajaran IPAS Kelas V SD N 1 Wonokerso - Najma Izzatuna Dauly; Meilan Tri Wuryani; Rachmat Imam Muslim; Dwi Cahaya Nurani (Universitas Sriwijaya in Collaboration with HDPGSDI (Himpunan Dosen PGSD Indonesia), 2024)
In implementing learning in elementary schools, especially in science and science subjects, there are several problems. This problem is considered to be one of the factors in reducing student learning outcomes. These problems can be problems originating from the teacher's way of teaching to the way students receive learning from the teacher. This research aims to analyze various problems experienced by teachers and students in science learning. The research was conducted in a qualitative descriptive form where this research was conducted on all class V students of SD N 1 Wonokerso, totaling 22 people as the population. The research instruments are observation guidelines, interviews and questionnaires. The results of research on problems that arise in science and science learning in this research include: teachers' classroom mastery that does not pay attention to the diversity of student characteristics, teachers' understanding of the independent curriculum is still lacking, teachers' creativity and understanding of learning models results in a lack of variation in learning, inappropriate use of media. even minimal use of media and students' lack of learning motivation in science learning. The solution to overcome this problem is that educators are expected to always be able to follow the curriculum that is being implemented, align the learning approach with the material being discussed so that students do not become passive, and can choose the right media and involve students during learning.